Experimental Study on Optimization of Transmission Efficiency based on the Different Type of Lubricant - Chen Zhao; Yang Jianjun; Chen Hongtao; Bai Bateer; Jiang Zheng (Jixie chuandong)
With the upgrading of environmental protection requirements and the development of automobile industry technology,more and more high demanding work focus on the improvement of automobile energy use.The fuel consumption especially for NEDC cycle is affected greatly by the transmission efficiency. An experimental study on the transmission efficiency improvement base on using of different type of lubricant is presented. The effect of the variables of input speed,input torque,and gear position on the efficiency is compared throughout the transmission performance testing and analyzing. The experiment study shows that the selecting optimized lubricant numbered with 2 has a noticeable improving on the transmission efficiency with an insignificant difference in the viscosity compared to the based type of lubricant. There is some difference between different gear positions in transmission efficiency,although in the improvement of efficiency the results are almost unchanged when it is replaced with different type of lubricant. It is showed that the input torque has a negative effect on the improvement for different type of lubricant because of the transmission efficiency increasing with the torque increasing. It is also showed that an average improvement of 2 percent point on the transmission efficiency as well as 3% improvement on the fuel consumption of NEDC cycle when selecting optimized lubricant numbered with 2 used in the vehicle test.